Keefektifan Ferri Chlorida (Fecl3) Dalam Menurunkan Kadar Chemical Oxygen Demand (Cod) Pada Limbah Cair Industri Batik Cv. Brotoseno Masaran Sragen - Sayuti, Putri Anggi (2016)
COD levels in wastewater which indicates that the higher the degree of pollution in the waters also high. Results wastewater COD content measurement batik CV. Brotoseno Masaran Sragen at 3936.00 mg / l, this value exceeds a predetermined quality standards. Decreased levels of COD can be done by coagulation, flocculation and sedimentation using ferric chloride (FeCl3). The purpose of this study to determine the effectiveness of ferric chloride (FeCl3) in reducing the levels of COD in wastewater batik industry in CV. Brotoseno Masaran Sragen. This research method True Experiment with pretest posttest study design with Control Group. The population in this study is the CV batik industrial wastewater. Brotoseno with the volume of wastewater each day ± 2.5 m3. The number of samples used is 24 liters. Quota sampling technique sampling. Statistical test using One Way Anova with data analysis p-0.000 (p <0.000), so that Ha is accepted. Statistical test results showed the effectiveness of the coagulant dose of ferric chloride (FeCl3) in the lower levels of COD. Coagulant dose of ferric chloride (FeCl3) is most effective at lowering levels of COD in industrial wastewater batik CV. Brotoseno Masaran Sragen is 4.5 g / l with effectiveness of 70.96% (1142.58 mg / l).